MANAJEMEN PERUBAHAN DI SEKOLAH: TANTANGAN DAN STRATEGI UNTUK MENCAPAI KUALITAS PENDIDIKAN YANG BERKELANJUTAN - Saptiani; Suidat; Agitsna Pradyta Maulidya; Siti Nurcholifia; Andi Maulana Sidik (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Change management in schools is crucial in addressing the rapid demands of change in the current global educational context. This study aims to identify effective strategies in change management within schools and analyze their impact on educational quality. The research method employed is a qualitative approach with an in-depth case study conducted at several urban secondary schools. The findings reveal that strong leadership, active stakeholder participation, and effective communication significantly contribute to the successful implementation of changes in the studied schools. The implications underscore the need for continuous training for staff and the development of policies that support school adaptation to changes. Sustainable and integrative strategies are necessary to enhance educational quality over the long term. This research is expected to provide new insights into the dynamics of change management in schools and support efforts towards achieving better education that is responsive to global changes.